138 In vivo localization of genetically engineered natural killer cells against glioblastoma using PET imaging. (10th December 2020) - Yun, Yeonhee; Wang, Jiao; Pollok, Karen; Sinn, Tony; Brutkiewicz, Randy; Matosevic, Sandro; Veronesi, Michael
Abstract : Background: Glioblastoma (GBM) is a deadly brain malignancy with a dismal prognosis. While immunotherapy holds great promise for GBM treatment, most have failed due to a suppressive tumor microenvironment (TME). Antigen heterogeneity and adenosine signaling are two immunosuppressive mechanisms in GBM. The CD73-adenosine axis plays a multifaceted role in GBM pathogenesis and drives the dysfunction of NK cells in GBM TME. 1, 3 Our NKG2D-chimeric antigen receptor (CAR)-natural killer (NK) cells have shown anti-tumor activity when combined with CD73 blockade in vivo. 2 To further extend the potency of these cells against GBM and address antigen heterogeneity in GBM, we combined the local blockade of CD73 with multi-antigen-targeting engineered NK cells. In order to improve treatment assessment, PET/MR imaging was employed to enable detailed, non-invasive assessment of tumor progression. Imaging assessment of adoptively-transferred CAR- NK cells was also developed to determine the fate of NK cell delivery to the tumor site over time. Methods: We generated multifunctional engineered NK (E-NK) cells that express an anti-CD73 scFv, which is cleavable by GBM-associated proteases, an NKG2D-CAR, as well as a GD2 CAR, which can actively target the GD2 antigen overexpressed on GBM (Figure 1 A). For E-NK cell radiolabeling, zirconium-89 (89Zr, ½ life = 78 Hr) radiotracer was attached covalently to the E-NK cell surface via conjugation with DFO-Bz-NCS in a range of doses from 50–600 µCi. Results: An optimal balance between labeling efficiency and cell viability was attained at 120 µCi 89Zr resulting in 39% labeling efficiency and 46% cell viability over for 48 hours. After labeling, the NK cells maintained their in vitro killing activity against GBM cells (figure 1 B). The 89Zr labeled E-NK cells were administered intravenously in mice containing intracranial GBM10 tumors at week 5 post-implant. PET imaging was performed at 1 and 2 days later and gamma imaging ex vivo at 4 days. Free 89Zr was visible diffusely throughout the body with low levels in the brain. The majority of 89Zr labeled E-NK cell groups localized to the lungs with detectable activity elsewhere in various organs (figure 1 C and 1D). Conclusions: We generated multifunctional E-NK cells which showed the improved killing of GBM cells using novel targeting approaches, including the blockade of CD73-mediated adenosinergic signaling. We also optimized E-NK cell radiolabeling with 89Zr for GB10 therapy in vitro and in vivo fate mapping against a xenograft of patient-derived GBM. Acknowledgements: We gratefully acknowledge the Walther Oncology Embedding Program, Indiana University Simon Cancer Center, and In Vivo Therapeutics Core. References: Wang J, Matosevic S. NT5E/CD73 as correlative factor of patient survival and natural killer cell infiltration in glioblastoma. J Clin Med 2019;8(10):1526. Wang J, Lupo KB, Chambers AM, Matosevic S. Purinergic targeting enhances immunotherapy of CD73+ solid tumors with piggyBac-engineered chimeric antigen receptor natural killer cells. J Immunother Cancer 2018;6(1):136. Yan A, Joachims ML, Thompson LF, Miller AD, Canoll PD, Bynoe MS. CD73 promotes glioblastoma pathogenesis and enhances its chemoresistance via A2B adenosine receptor signaling. J Neurosci 2019;39(22):4387. Flink J, Muzi M, Peck M, Krohn K. Multimodality brain tumor imaging: mr imaging, PET, and PET/MR imaging. J Nucl 2015;5(10):1554–1561.